2020
DOI: 10.3390/molecules25041004
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Marine Seaweeds as Prebiotics: A Review

Abstract: Human gut microbiota plays an important role in several metabolic processes and human diseases. Various dietary factors, including complex carbohydrates, such as polysaccharides, provide abundant nutrients and substrates for microbial metabolism in the gut, affecting the members and their functionality. Nowadays, the main sources of complex carbohydrates destined for human consumption are terrestrial plants. However, fresh water is an increasingly scarce commodity and world agricultural productivity is in a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 115 publications
0
84
0
Order By: Relevance
“…Other important Firmicutes genera are Lactobacillus, Bacillus, Enterococcus and Ruminococcus [20]. Regarding the phylum Bacteroidetes, the predominant genus is Bacteroides (about 90% of total Bacteroidetes), Prevotella also being a relevant genus [5]. The phylum Actinobacteria is proportionally less abundant and is mainly represented by the genus Bifidobacterium [8].…”
Section: Influence Of the Gut Microbiota On Human Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Other important Firmicutes genera are Lactobacillus, Bacillus, Enterococcus and Ruminococcus [20]. Regarding the phylum Bacteroidetes, the predominant genus is Bacteroides (about 90% of total Bacteroidetes), Prevotella also being a relevant genus [5]. The phylum Actinobacteria is proportionally less abundant and is mainly represented by the genus Bifidobacterium [8].…”
Section: Influence Of the Gut Microbiota On Human Healthmentioning
confidence: 99%
“…Thus, conventional agriculture presents concerns. For example, fresh water (an essential resource) is a very scarce commodity, and progressive desertification of the earth's surface is taking place and will probably be aggravated in the future by global warming and desertification process [5]. According to the Food and Agriculture Organization of the United Nations (FAO) [6], it is expected a progressive decline in global agricultural productivity of about 1% per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue has received remarkably positive feedback, with many contributions submitted by numerous geographically diverse scientists, resulting in a collection of 10 publications, including two exhaustive review articles [9][10][11][12][13][14][15][16][17][18]. Among the contributing authors, authors can be found from Asia (China, India, and Uzbekistan), Europe (Spain), South America (Brazil and Chile) and North America (Mexico).…”
mentioning
confidence: 99%
“…In view of the results, both G. corticata and G. edulis contain important nutrients for human health and are possible natural functional foods [15]. More generally, a wide review about the current knowledge surrounding the impacts of seaweeds and their derived polysaccharides on the human microbiota is also presented, in which potential benefits against chronic non-transmissible diseases were discussed [16].…”
mentioning
confidence: 99%